2002
DOI: 10.1037/0022-0167.49.1.14
|View full text |Cite
|
Sign up to set email alerts
|

The career development of Mexican American adolescent women: A test of social cognitive career theory.

Abstract: This study tested R. W. Lent, S. D. Brown, and G. Hackett's (1994) model of career choice with 364 Mexican American adolescent women. Path analyses were run to determine the influence of contextual and social cognitive variables on career aspiration, career choice prestige, and traditionality. Partial support for the model was evidenced as nontraditional career self-efficacy, parental support, barriers, acculturation, and feminist attitudes predicted career choice prestige. Acculturation, feminist attitudes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
339
4
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(380 citation statements)
references
References 67 publications
(180 reference statements)
32
339
4
5
Order By: Relevance
“…That is, although a few studies of SCCT have included occupational prestige (e.g., Flores & O'Brien, 2002;Tang, Fouad, & Smith, Prestige Interests and Choice Goals 19 1999), no prior studies have used prestige-specific measures of self-efficacy, outcome expectations, interests, and choice goals to assess SCCT-implied relationships among the set of prestige variables. Understanding African American women's career development along the prestige dimension may be particularly important due to trends of employment in lower-prestige occupations for this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, although a few studies of SCCT have included occupational prestige (e.g., Flores & O'Brien, 2002;Tang, Fouad, & Smith, Prestige Interests and Choice Goals 19 1999), no prior studies have used prestige-specific measures of self-efficacy, outcome expectations, interests, and choice goals to assess SCCT-implied relationships among the set of prestige variables. Understanding African American women's career development along the prestige dimension may be particularly important due to trends of employment in lower-prestige occupations for this population.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, self-efficacy and outcome expectations influence the individual's vocational interests and other career outcomes such as career choice, both directly and through a sequential pathway. Given SCCT's attention to contextual as well as internal person variables, this theory has been applied to ethnic minorities and women in both conceptual literature (e.g., Byars & Hackett, 1998) and empirical studies (e.g., Flores & O'Brien, 2002;Flores, Robitschek, Celebi, Andersen, & Hoang, 2010;Lent, Sheu, Gloster, & Wilkins, 2010;Nauta & Epperson, 2003;Navarro, Flores, & Worthington, 2007;Rivera, Chen, Flores, Blumberg, & Ponterotto, 2007). However, much of the traditional SCCT research focusing exclusively on African Americans has been conducted in math and science-related domains (Lent et al, 2005 because African Americans are underrepresented in STEM occupations (National Science Foundation, 2013).…”
Section: Prestige Interests and Choice Goalsmentioning
confidence: 99%
“…Así, por ejemplo, Flores y O'Brien (2002) verifi can que las creencias de autoefi cacia infl uyen en el interés. Del mismo modo, Nauta y Epperson (2003), con una muestra de alumnas de secundaria con interés por la ciencia y la tecnología, corroboraron que sus creencias de autoefi cacia infl uían en su interés por la ciencia y que este interés predecía sus metas para persistir en los estudios científi cos-tecnológicos.…”
Section: Introductionunclassified
“…Careers in science or technology domains are highly valued and prestigious indicators of social standing in Asian culture, and therefore Asian female students in the US are likely to be encouraged to pursue such a career. However, Leung [9] warned that Asian youth's career choices may be limited if those choices are influenced solely by reputation as this may lead to career decision-making incompatible with their interests and competences.…”
Section: The Implications Of Self-efficiencymentioning
confidence: 99%
“…Besides influencing their personal development, background factors such as family of origin, socioeconomic status and level of education, have an impact on individuals' career preferences and decision-making as well [9]. Studies that have addressed this issue with regard to Asian youth have reported that the individuals' career ambitions and choices were heavily shaped by their parents [10].…”
Section: Background and Family Influencesmentioning
confidence: 99%